“I am Sámi, but I am not a Sámi”: Coastal Sámi students’ articulations of identity in a colonial-blind Norwegian state - Stenseth, Anna-Maria (Nordic Journal of Comparative and International Education (NJCIE), 2023)
This article gives voice to coastal Sámi students and explores their negotiations over being Sámi or Norwegian within the Norwegian education system. Through interviews, students share insights on the extent to which education focuses on Sámi issues and reflect upon their identity. The article explores how youths negotiate personal identity within pre-existing structures by employing Archer’s theory on structure and agency as a backdrop. The changing phases in how ‘western’ societies view indigenous practices and knowledges are applied together with (de)colonial perspectives to understand (colonial) structures. Some key findings are that the coastal Sámi students’ identity negotiations are complex, as official discourses seem to restrict them from identifying as ‘real’ Sámi, and that the local Sámi is within a discursive void due to unintended consequences resulting from the unification in the centralised education system. In focusing on students and using the educational system as a backdrop, this article seeks to deepen the understanding of how society and the educational system in particular condition students’ notions of what it entails to be Sámi and how students negotiate their identity.